2020
DOI: 10.33151/ajp.17.804
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Competence of Undergraduate Paramedic Student Practice: A Preliminary Evaluation of the Australasian Paramedic Competency Assessment Tool

Abstract: Introduction With the recent introduction of registration for paramedics, and an absence of assessment tools that align undergraduate paramedic student practice to competency standards, this pilot study undertook to develop and evaluate a competency assessment tool designed to provide a standardised approach to student competency assessment. This paper reports the first part of a two-part enquiry evaluating the efficacy of the Australasian Paramedic Competency Assessment Tool (APCAT) to assess the practice com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 19 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…As a substantive theory, the PAP has implications for the assessment of competence generally as the profession moves to apply practice standards across the service. PAP highlights situations that raise concern about assessment practices that may compromise the rigour and validity of assessment outcomes, 53,54,59 and exposes the delicate balance between the participants' views and expectations surrounding safe practice, competency assessment practices, the environment in which assessment takes place, and the impact that the realities of practice have on assessment outcomes. 1,34 PAP contributes to paramedic professional knowledge by providing insights into current practices and increasing understanding about how students are assessed, and which may provide direction and inform policy and procedure development.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As a substantive theory, the PAP has implications for the assessment of competence generally as the profession moves to apply practice standards across the service. PAP highlights situations that raise concern about assessment practices that may compromise the rigour and validity of assessment outcomes, 53,54,59 and exposes the delicate balance between the participants' views and expectations surrounding safe practice, competency assessment practices, the environment in which assessment takes place, and the impact that the realities of practice have on assessment outcomes. 1,34 PAP contributes to paramedic professional knowledge by providing insights into current practices and increasing understanding about how students are assessed, and which may provide direction and inform policy and procedure development.…”
Section: Discussionmentioning
confidence: 99%
“…44 As literature is considered a source of data, it is methodologically appropriate that in this study it has been woven into the substantive theory and is reported here in conjunction with the Paramedic Assessment Process. 19 Our sample included lecturers and sessional staff at universities, and on-road paramedics involved in the summative competency assessment of final-year paramedic students in New Zealand and Australia. For the purposes of this enquiry, an assessor is defined as those individuals who assess undergraduate students in universities and ambulance services in Australia and New Zealand.…”
Section: Methodology Methods and Analysismentioning
confidence: 99%
See 3 more Smart Citations